Training, supervision and performance of Community Health Workers in the delivery of ear and hearing care to 321 community members in rural Uganda. (17th August 2021) - O'Donovan, James; Nakku, Doreen; Nyanzi, Daniel; Nakasagga, Esther; Hamala, Rebecca; Namanda, Allan S.; Kabali, Kenneth; Winters, Niall; Chadha, Shelly; Bhutta, Mahmood F.
Abstract: Objectives: Community Health Workers are one way to address the shortage of ear and hearing care specialists in low‐resource settings. However, there are few reports evaluating training and service delivery by Community Health Workers. Design, setting and participants: We trained 13 Community Health Workers in primary ear and hearing care in Mukono District, Uganda. Community Health Workers attended a two‐day training workshop and received remote supervision thereafter during service delivery in the community. An ear camp was held at the local health centre every two months, where a local ENT specialist could assess referred cases. Main outcome measures: Clinical and diagnostic skills and decision‐making were assessed using an Objective Structured Clinical Examination, with scores recorded at baseline and six months. Service delivery was evaluated by analysing the following: (i) number of individuals evaluated; (ii) treatments delivered; (iii) cases referred for specialist opinion; (iv) proportion of appropriately referred cases; and (v) agreement between Community Health Worker and specialist diagnosis. Results: Observed Structured Clinical Examination scores were high and stable for six months. 312 individuals were screened in the community by the Community Health Workers, with 298 classified as having an abnormality. Care was delivered in the community to 167 of these, and the remaining 131 referred to the ear camp. Diagnostic agreement was 39%, but 98% of referrals were deemed "appropriate" by the ENT specialist. 27 individuals self‐presented to the ear camp without prior assessment by a Community Health Worker, and 97% of these were deemed appropriate. Conclusion: Trained Community Health Workers can play an important role in delivering ear and hearing services. Future work should look to explore this model in other contexts and/or compare it to other models of service delivery.